A new measuring method for friction factor by using ring with inner boss compression test - Hu, Chengliang; Yin, Qiang; Zhao, Zhen; Ou, Hengan (Elsevier, 2017)
To overcome the disadvantage of the bulging effect due to non-uniform deformation in dimension measurement of the conventional ring compression test (RCT), a new measuring method for the friction factor called ring compression test with inner boss (RCT-IB) was proposed. The compression behavior of the ring with an inner boss was investigated and results showed that the change of inner boss was sensitive to friction. The non-concave profile of inner boss allows the dimensional changes to be easily and precisely measured. The calibration curves of RCT-IB were constructed and compared with those of RCT showing similar level of sensitivities at most friction conditions. The RCT-IB method was successfully used to measure the friction factors under four different lubricating conditions.